2010
DOI: 10.1055/s-0030-1249877
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Epigallocatechin Gallate Inhibits Insulin Stimulation of Adipocyte Glucose Uptake via the 67-Kilodalton Laminin Receptor and AMP-Activated Protein Kinase Pathways

Abstract: Insulin and (-)-epigallocatechin gallate (EGCG) are reported to regulate obesity and fat accumulation, respectively. This study investigated the pathways involved in EGCG modulation of insulin-stimulated glucose uptake in 3T3-L1 and C3H10T1/2 adipocytes. EGCG inhibited insulin stimulation of adipocyte glucose uptake in a dose- and time-dependent manner. The concentration of EGCG that decreased insulin-stimulated glucose uptake by 50-60% was approximately 5-10 µM for a period of 2 h. At 10 µM, EGCG and gallic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Several studies have investigated whether natural products inhibit adipogenesis or enhance lipolysis to reduce the amount of adipose tissue. A major component of flavonoids in green tea, (−)-epigallocatechin gallate (EGCG), was shown to significantly reduce insulin-stimulated glucose uptake through the 67LR, known as the EGCG receptor, and AMPK pathways at 5-10 μM in 3T3-L1 and C3H10T1/2 adipocytes (Hsieh et al 2010). Other natural compounds, such as genistein in soy, xanthohumol in beer hops, resveratrol in grapes, and curcumin in turmeric, were reported to exhibit adipogenesis inhibition activities by reducing peroxisome proliferator-activated receptor gamma (PPARγ ) expression and/or activating AMPK in adipocytes (Andersen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated whether natural products inhibit adipogenesis or enhance lipolysis to reduce the amount of adipose tissue. A major component of flavonoids in green tea, (−)-epigallocatechin gallate (EGCG), was shown to significantly reduce insulin-stimulated glucose uptake through the 67LR, known as the EGCG receptor, and AMPK pathways at 5-10 μM in 3T3-L1 and C3H10T1/2 adipocytes (Hsieh et al 2010). Other natural compounds, such as genistein in soy, xanthohumol in beer hops, resveratrol in grapes, and curcumin in turmeric, were reported to exhibit adipogenesis inhibition activities by reducing peroxisome proliferator-activated receptor gamma (PPARγ ) expression and/or activating AMPK in adipocytes (Andersen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that a 67-kDa laminin receptor (67LR), as the cell surface EGCG receptor, may be involved in mediating these actions of EGCG (22)(23)(24)(25). Moreover, EGCG is also believed to exert an Epigallocatechin-3-gallate prevents TNF-α-induced NF-κB activation thereby upregulating ABCA1 via the Nrf2/Keap1 pathway in macrophage foam cells anti-atherosclerotic effect via anti-inflammatory and metabolic regulation activities (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Though the interactions between EGCG and insulin have been extensively studied in vivo [22][23][24][25], the molecular interactions between EGCG and insulin are still unclear. In this work, we have found that EGCG at concentrations of 1-5 mM induces insulin to aggregate into reversible globular precipitate.…”
Section: Introductionmentioning
confidence: 99%